Oral dextran sulfate sodium administration induces peripheral spondyloarthritis features in SKG mice accompanied by intestinal bacterial translocation and systemic Th1 and Th17 cell activation - Tabuchi, Yuya; Katsushima, Masao; Nishida, Yuri; Shirakashi, Mirei; Tsuji, Hideaki; Onizawa, Hideo; Kitagori, Koji; Akizuki, Shuji; Nakashima, Ran; Murakami, Kosaku; Murata, Koichi; Yoshifuji, Hajime; et al. (Arthritis research & therapy, 2022)
Background Spondyloarthritis (SpA) is an autoimmune and autoinflammatory musculoskeletal disease characterised by systemic enthesitis. Recent research has focused on subclinical inflammatory bowel disease (IBD) in SpA pathogenesis. SKG mice, harbouring the Zap70 W163C mutation, increase autoreactive Th17 cells intrinsically, and in a conventional environment, they exhibit spontaneous arthritis with fungal factors. Under SPF conditions, they show SpA features, including enteritis, after peritoneal injection of β-1,3-glucan. This study aimed to clarify whether oral dextran sulfate sodium (DSS) administration, utilised in IBD model mice, can provoke SpA features in SKG mice under SPF conditions, focusing on the relationship between gut microorganisms and SpA pathogenesis. Methods BALB/c and SKG mice were administered oral DSS, and their body weights, arthritis, and enthesitis scores were recorded. In another cohort, antibiotics (meropenem and vancomycin) or an anti-fungal agent (amphotericin B) was administered orally before DSS administration. The splenic Th1 and Th17 cell populations were examined before and after DSS administration using flow cytometry. Furthermore, the amount of circulating bacterial DNA in whole blood was measured by absolute quantitative polymerase chain reaction (qPCR), and the number and characteristics of bacterial species corresponding to these circulating DNA were analysed by next-generation sequencing (NGS). Results Ankle enthesitis as a peripheral SpA feature was elicited in half of DSS-administered SKG mice, and none of the BALB/c mice. Pre-administration of antibiotics suppressed enthesitis, whilst an anti-fungal agent could not. Th1 and Th17 cell levels in the spleen increased after DSS administration, and this was suppressed by pre-administration of antibiotics. SKG mice have a larger amount of bacterial DNA in whole blood than BALB/c mice before and 1 day after the initiation of DSS administration. The number of bacterial species in whole blood increased after DSS administration in BALB/c and SKG mice. Some genera and species significantly specific to the DSS-treated SKG mouse group were also detected. Conclusion Oral DSS administration alone elicited peripheral enthesitis in SKG mice with bacterial translocation accompanied by increased splenic Th1 and Th17 cell levels. Pre-administration of antibiotics ameliorated these DSS-induced SpA features. These findings suggest that intestinal bacterial leakage plays a pivotal role in SpA pathogenesis.